Didactic Opportunities for Using National Artistic Traditions in Visual Arts Lessons - Gadoyev Ibrohim Niyozovich (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: This article examines the pedagogical potential of integrating national artistic traditions into visual arts lessons. Various teaching strategies, interactive methods, and practical exercises are analyzed to enhance students’ artistic competencies. The study highlights how the use of traditional motifs and cultural elements can develop students’ creative thinking, aesthetic appreciation, and independent artistic skills.